2020
DOI: 10.1002/gepi.22339
|View full text |Cite
|
Sign up to set email alerts
|

A principal component approach to improve association testing with polygenic risk scores

Abstract: Polygenic risk scores (PRSs) have become an increasingly popular approach for demonstrating polygenic influences on complex traits and for establishing common polygenic signals between different traits. PRSs are typically constructed using pruning and thresholding (P+T), but the best choice of parameters is uncertain; thus multiple settings are used and the best is chosen. Optimization can lead to inflated Type I error. Permutation procedures can correct this, but they can be computationally intensive. Alterna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…Similar to pseudovalidation approaches, no tuning sample is required when assuming an infinitesimal model. Rather than selecting a single tuning parameter, some studies have suggested that combining polygenic scores across p-value thresholds whilst taking into account their correlation using either PCA or model stacking can improve prediction [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to pseudovalidation approaches, no tuning sample is required when assuming an infinitesimal model. Rather than selecting a single tuning parameter, some studies have suggested that combining polygenic scores across p-value thresholds whilst taking into account their correlation using either PCA or model stacking can improve prediction [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PRSs were constructed using PRSice2 [ 42 ] to prune ( r 2 > 0.1 within a 500 kb window) and restrict SNPs to a given p value threshold (p t = 0.0001, 0.001, 0.01, 0.05, 0.1, 0.2, 1), with SNP alleles weighted by their log(HR) estimates. We then performed a principal component analysis (PCA) on the set of PRSs estimated at different p value thresholds and used the first PRS principal component to test for association with the outcome; this PRS-PCA strategy eliminates the multiple testing across PRSs based on different p value thresholds [ 43 ]. The PRSs for TR and THR were tested for association with the respective treatment outcome in each left out dataset using Cox proportional hazards models, and the results from the analyses of the three datasets were meta-analyzed to assess overall PRS prediction of treatment response.…”
Section: Methodsmentioning
confidence: 99%
“…Following QC, polygenic risk scores (PRS) were derived using common (>5% minor allele frequency; MAF), well-imputed (INFO>0.8) variants using PLINK version 1.9 [ 35 ], based on large discovery GWAS of primarily European ancestry, with no overlap with the target sample: ADHD (19,099 cases and 34,194 controls) [ 36 ], anxiety disorders (31,977 cases, 82,114 controls) [ 10 ], MDD (59,851 cases and 113,154 controls) [ 11 ], schizophrenia (67,390 cases and 94,015 controls) [ 37 ], ASD (18,382 cases, 27,969 controls) [ 38 ], and bipolar disorder (20,352 cases and 31,358 controls) [ 39 ]. For each discovery GWAS, PRS were calculated using 7 different p-value thresholds and the first principal component based on the correlation matrix for these PRS was extracted and analysed, using the PRS-PCA approach [ 40 ]; see details in S1 Text in S1 File . The PRS were standardised to be z-scores for each analysis.…”
Section: Methodsmentioning
confidence: 99%